Iron accumulation in the basal ganglia in Huntington's disease: cross-sectional data from the IMAGE-HD study. Issue 5 (7th May 2015) - Domínguez D, Juan F; Ng, Amanda C L; Poudel, Govinda; Stout, Julie C; Churchyard, Andrew; Chua, Phyllis; Egan, Gary F; Georgiou-Karistianis, Nellie
Abstract : Objectives: To measure iron accumulation in the basal ganglia in Huntington's disease (HD) using quantitative susceptibility mapping (QSM), and to ascertain its relevance in terms of clinical and disease severity. Methods: In this cross-sectional investigation, weighted imaging was undertaken on 31 premanifest HD, 32 symptomatic HD and 30 control participants as part of the observational IMAGE-HD study. Group differences in iron accumulation were ascertained with QSM. Associations between susceptibility values and disease severity were also investigated. Results: Compared with controls, both premanifest and symptomatic HD groups showed significantly greater iron content in pallidum, putamen and caudate. Additionally, iron accumulation in both putamen and caudate was significantly associated with disease severity. Conclusions: These findings provide the first evidence that QSM is sensitive to iron deposition in subcortical target areas across premanifest and symptomatic stages of HD. Such findings could open up new avenues for biomarker development and therapeutic intervention.